The Effects of Public Perception and Application of Good Governance Principles on Organizational Performances (A Case Study on the One-Stop-Integrated-Services of the Investment Agency of Dki Jakarta Province) - Prihadini, Diana; Ayu, Renisya; Andayani, Wuwuh; Krishantoro, Krishantoro; Rofikah, Rofikah (Budapest International Research and Critics University, 2021)
This study was aimed at analyzing the effects of public perception and application of good governance principles, both partially and simultaneously, on an organizational performance. The research was conducted by using a questionnaire survey method. The samples in this study were 53 people and the sampling technique was simple random sampling. The data analyses were the correlation and regression analysis, t-test, F-test, and determination coefficient test. The results of the study proved that the public perception and application of good governance principles; both partially and simultaneously; had a positive and significant impact on organizational performance. The public perception had an effect of 60.5%, while the application of good governance principles had an effect of 55.1%. Meanwhile, those two independent variables had an effect of 88.6% on the dependent variable.